Analisis Kriminologis terhadap Penyebaran Konten Pornografi LGBT di Dunia Maya (Studi Putusan Pengadilan Nomor: 343/Pid.Sus/2020/Pn.Pbr) - Yaswirman Yaswirman; Nilma Suryani; Vivi Dwi Yulian Benni (UNES Law Review, 2023)
In essence, social media gave birth to new concerns, including the emergence of the development of the spread of pornography with pornographic sites in sharing various types of site views which are very tempting and have a major influence on the nation's morals and personality which will have a negative impact on Indonesia so that it threatens life and social order. Indonesian society. The development of pornography in society has also resulted in an increase in immoral acts. Related to the Internet and communication tools, of course very closely related to Cybercrime (Crime in cyberspace). According to the Organization of European Community Development (OECD) Cybercrime is all forms of illegal access to a data transmission. That is, all types of illegal activity in a computer system is a crime. In this thesis entitled "Criminological Analysis of the Spread of LGBT Pornographic Content in Cyberspace (Study of Court Decisions Number: 343/Pid.Sus/2020/PN.Pbr)".)" discusses the problem, namely: What are the factors that cause the spread of LGBT pornographic content in cyberspace and what is the modus operandi of perpetrators in spreading LGBT pornographic content in cyberspace. The method used to answer the problems mentioned above. In terms of the type of data studied, this study uses two types of research, namely normative juridical research that is analytically descriptive by reviewing court decisions and analyzing them. The results of the research namely; the factors that led to the spread of LGBT pornographic content in cyberspace were technological sophistication, sexual needs, lack of attention in the field of religion, and weak attention from the government. The perpetrator's modus operandi in spreading LGBT pornographic content is none other than because the perpetrator wants to vent his sexual desires and inform social media that he is gay.